Biocompatibility performance evaluation of high flux hydrophilic CO3Ap/HAP/PSF composite membranes for hemodialysis application. Issue 8 (30th March 2021) - Zaman, Shafiq Uz; Saif‐ur‐Rehman,; Zaman, Muhammad Khaliq U; Arshad, Amber; Rafiq, Sikander; Muhammad, Nawshad; Saqib, Sidra; Jamal, Muddasar; Wajeeh, Salman; Imtiaz, Sania; Sadiq, Muhammad Tahseen
Abstract: Carbonate apatite/hydroxyapatite (CO3Ap/HAP) additive was obtained by calcination of wasted chicken bones at 900°C. Intermolecular attraction exists between CO3Ap/HAP additive and blended polysulfone (PSF) polymer. Electron dispersive X‐ray (EDX) and FTIR analysis were carried out to check the elemental composition and bonding chemistry of prepared additive. The instantaneous demixing process generated consistent finger‐like networks in CO3Ap/HAP/PSF‐based composite membranes while sponge‐like structure was shown by PSF as revealed by SEM images. The increase in weight % of additive loading is also confirmed by EDX analysis. Furthermore, the interaction mechanism of CO3Ap/HAP additive with polysulfone medium was analyzed by FTIR exploration. The water absorption experiment defined a 93% expansion in hydrophilic performance. Change in porosity occurs with additive loading and pure water permeation flux improved up to 11 times. Approximately, antifouling results revealed that 87% of water flux was recovered after treating with a protein solution, whereas a 30% improvement in antifouling capability in case of bovine serum albumin solution occurred. In vitro cytotoxicity, and clotting times study was carried out to evaluate virulent behavior and anticoagulation activity of formulated membranes. Abstract : Successful fabrication of CO3Ap/HAP/PSF composite membranes, and surface chemistry of membrane showing resistance towards protein albumin, nonvirulent behavior, extended PT, TT times, and removal aptitude towards uremic toxins.